SPECIAL TECHNOLOGIES OF APPLYING THERMAL REGENERATIVE COATINGS - Artemchuk, V. V. (Science and Transport Progress, 2010)
Features of technologies of putting the gas-thermal coatings are considered in the article. Some examples of using the modern sprayed materials are presented as well as the comparative analysis of basic methods of gas-thermal spraying is conducted on some indices. The influence of some technologic factors on the quality indices of processes of gas-thermal spraying is demonstrated.